(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
In the current era of globalization, the issue of interlinguistic relations and translation is of particular importance. Studying lexical coordination between English and Uzbek languages serves to master these two languages and improve intercultural communication. This article examines the similarities and differences of word substitutes in English and Uzbek, the problems that arise in the translation process, and their practical importance for language learners